Aplikasi Monitoring Laporan Data Hasil Pengolahan TBS Kelapa Sawit Berbasis Mobile Pada PT. Perkebunan Nusantara VII - Haldian, Haldian; Arifin, Oki; Kenali, Eko Win (Intechno Journal : Information Technology Journal, 2023)
The process of recording data processing reports from units to the PTPN VII head office has used a website-based application. This allows each unit to upload a report of processing data. In an effort to optimize applications, especially in presenting information that can be accessed in real-time for stakeholders to report palm oil processing results, it is necessary to develop a mobile-based application. At PTPN VII. This data collection activity was carried out at PTPN VII, Bandar Lampung head office from March to June 2023. The process of monitoring reports on processing data for Oil Palm Fresh Fruit Plants (FFB) can measure the quality and quantity of processing, as well as make strategic decisions in making decisions quickly and efficiently. accurate. The development of this application uses the Flutter framework, the PHP programming language and the MySql database. The results of the data obtained are the Mobile-Based Palm Oil FFB Processing Data Report Monitoring Application at PTPN VII.